Medium term results of lung transplantation for end stage pulmonary sarcoidosis. Issue 4 (1st April 1998) - Walker, Stuart; Mikhail, Ghada; Banner, Nicholas; Partridge, John; Khaghani, Asghar; Burke, Margaret; Yacoub, Magdi
Abstract : BACKGROUND: Lung transplantation is an accepted therapeutic option for patients with end stage pulmonary sarcoidosis. However, the medium term outcome of transplantation in this patient group is unknown. METHODS: This study was performed to evaluate our experience with lung transplantation for end stage pulmonary sarcoidosis. Between July 1988 and July 1997 12 patients (nine men) underwent lung transplantation for sarcoidosis at our institution. Ten underwent single lung transplantation and two double lung transplantation. RESULTS: Survival at three and five years was 70% and 56%, respectively. Three patients developed obliterative bronchiolitis at six, 18, and 45 months. One died at the time of retransplantation. Sarcoid granulomas have recurred in the donor organ in three patients. In one the development of granulomas has been associated with clinical deterioration, necessitating retransplantation. Mean (SD) forced expiratory volumes in one second at three and five years were 1.37 (0.67) l and 1.34 (0.13) l, respectively. CONCLUSIONS: Lung transplantation is a viable option for patients with end stage pulmonary sarcoidosis. The medium term results are comparable with patients undergoing lung transplantation for other indications. Despite histological recurrence of sarcoidosis, the risk of clinically important recurrence is low.